2022
DOI: 10.3389/fphar.2022.1027553
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide C slows the progression of osteoarthritis by activating Nrf2/HO-1 and blocking the NF-κB pathway

Abstract: Osteoarthritis (OA) is driven by chronic low-grade inflammation and subsequent cartilage degradation. OA is the most prevalent degenerative joint disease worldwide, and its treatment remains a challenge. The aim of this study was to explore the potential effects and mechanism underlying the anti-OA properties of ginkgolide C (GC). Protective effects of GC on hydrogen peroxide (H2O2)-treated rat chondrocytes were evaluated using ELISA, qPCR, western blot analysis, flow cytometry, ROS detection and immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Our results showed that Nrf2 and HO-1 expressions were activated whereas NF-κB expression was suppressed in the cells with increasing AA drug concentration. Ma et al also demonstrated that Nrf2/HO-1 negatively regulated the activation of the proinflammatory signaling molecule NF-κB (Ma et al, 2022), thus inhibiting RA-FLS proliferation as well as promoting RA-FLS apoptosis (Nejatbakhsh Samimi et al, 2020). Nrf2 is an important intracellular transcription factor that is sensitive to redox reaction (Yan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Nrf2 and HO-1 expressions were activated whereas NF-κB expression was suppressed in the cells with increasing AA drug concentration. Ma et al also demonstrated that Nrf2/HO-1 negatively regulated the activation of the proinflammatory signaling molecule NF-κB (Ma et al, 2022), thus inhibiting RA-FLS proliferation as well as promoting RA-FLS apoptosis (Nejatbakhsh Samimi et al, 2020). Nrf2 is an important intracellular transcription factor that is sensitive to redox reaction (Yan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For the in vitro model of OA-like ACs, H 2 O 2 (Jing Rui, China) was added to the ACs medium to induce ACs expressing an OA-like phenotype (ACs + H 2 O 2 ) ( Ma et al, 2022 ; Chen et al, 2023 ; Yagi et al, 2023 ). Briefly, the ACs were treated with the conditioned medium for 24 h. Then, the OA-like ACs were co-cultured with different MSCs before and after IL-1β treatment (UC-MSCs, UC-MSCs + IL-1β, FP-MSCs, FP-MSCs + IL-1β, CPJ-MSCs, CPJ-MSCs + IL-1β).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the extraction of rat cartilage tissue proteins was performed by referring to a previous study. 41,42 At the end of 8 weeks of OLA intervention, the dissected cartilages were removed from the right knee joint of the rat (use a scalpel [11#] to cut the cartilage multiple times) and homogenized in 1 mL PBS ( pH 7.4) containing protease inhibitors by shaking with 1.5 mm glass beads in a Mini-BeadBeater (BioSpec, USA) at 4800 oscillations min −1 for 3 min. The tissue homogenates were immediately centrifuged twice at 12 000g for 15 min at 4 °C to isolate the supernatant.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%